2003
DOI: 10.1038/nsmb711
|View full text |Cite
|
Sign up to set email alerts
|

Identification of small molecule inhibitors of anthrax lethal factor

Abstract: The virulent spore-forming bacterium Bacillus anthracis secretes anthrax toxin composed of protective antigen (PA), lethal factor (LF) and edema factor (EF). LF is a Zn-dependent metalloprotease that inactivates key signaling molecules, such as mitogen-activated protein kinase kinases (MAPKK), to ultimately cause cell death. We report here the identification of small molecule (nonpeptidic) inhibitors of LF. Using a two-stage screening assay, we determined the LF inhibitory properties of 19 compounds. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
160
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(170 citation statements)
references
References 24 publications
7
160
1
2
Order By: Relevance
“…We succeeded in detecting LF inhibition by 19 F-NMR using the fluorinated peptide Ac-A-R-R-K-K-V-Y-P-NH-Ph-CF 3 as an enzymatic substrate (24,25). Cleavage of the peptide occurring at the Pro-Xxx position deeply affects chemical environment of 19 F nuclei because of the conversion of the amide functionality into an amine with release of pCF 3 -aniline.…”
Section: Resultsmentioning
confidence: 99%
“…We succeeded in detecting LF inhibition by 19 F-NMR using the fluorinated peptide Ac-A-R-R-K-K-V-Y-P-NH-Ph-CF 3 as an enzymatic substrate (24,25). Cleavage of the peptide occurring at the Pro-Xxx position deeply affects chemical environment of 19 F nuclei because of the conversion of the amide functionality into an amine with release of pCF 3 -aniline.…”
Section: Resultsmentioning
confidence: 99%
“…EF is an adenylate cyclase, and LF is a protease that cleaves mitogen-activated protein kinase kinases. The enzymatic activities of these proteins contribute to disease progression in several ways and at different stages of infection (16).Several anthrax-toxin inhibitors have been described that interfere with different steps in this intoxication pathway (8,11,12,16,(20)(21)(22)(23)(24)(25)(26), but none has targeted the host receptors. Here, we describe the development of a polyvalent receptor-directed anthrax-toxin inhibitor that binds both receptors and protects animals from toxin challenge.…”
mentioning
confidence: 99%
“…FRET studies using small peptides demonstrated 100-fold faster cleavage of a consensus cleavage sequence (derived from MAPKK cleavage sites) when compared with natural sites (8). Using FRET peptides, small molecule inhibitors with K i 's ranging from 0.5 lM to 7 nM have been isolated (13,14). Absorbance methods using p-nitroanilide coupled peptides in HTS screens were used to select the peptide inhibitor IN-2-LF (9).…”
mentioning
confidence: 99%